Special and overall endurance rates in team athletes of different specializations and qualifications - Maksimenko, I. G.; Maksimenko, G. N.; Voronin, I. Yu.; Zilina, L. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to evaluate and compare the special and overall endurance rates in the representatives of various sports games with the qualifications from Class III to Masters of Sport.